Prognostic value of pharmacotherapy in patients with atrial fibrillation after radiofrequency ablation - M. S. Brynza (Zaporozhye State Medical University, 2021)
The aim of the work: to evaluate the prognostic effect of pharmacotherapy before and after radiofrequency ablation (RFA) in patients with atrial fibrillation (AF) on all-cause mortality, supraventricular arrhythmia recurrence and non-fatal cardiovascular events.